Pressure sensitive adhesive closing and sealing tapes for packaging Part 1. Specification for polypropylene, regenerated cellulose and unplasticized PVC tapes (BSI, 1984)
Requirements for pressure sensitive adhesive tapes based on polypropylene, regenerated cellulose and unplasticized PVC used for closing and sealing inner and outer containers normally used in packaging